Oliver dear - Antonio, Matthew, author; Becker, Leslee, advisor; Doenges, Judy, committee member; Prince, Eric, committee member (Colorado State University. Libraries, 2012)
Here's what I do: I use the surrealist technique of automatic writing to generate raw material. I then take that raw material and sift through it for elements that seem to be of particular concern to me. These elements will be repeated or related images, events, characters, or settings. Once I have this refined material, I analyze it to discover what it is about these elements that I'm trying to tell myself is of merit. Characters emerge, as do setting and narrative. This is the mechanism. This approach is not surrealism. It uses surrealist methods, though in a way I would imagine to be abhorrent to any real surrealist. My approach, however, does create a sense of the unreal, of impossible events and places. In my novel, Oliver Dear, the narrative revolves around a single event experienced, perhaps, by the protagonist as a child. I dissected this single event into the elements of image and event and personified those elements as characters that the protagonist as an adult encounters in the impossible setting of the apartment building. He encounters a story in fits and starts, each element out of context and an unreal narrative is established. Here's why I do it: An unreal narrative is my goal because it's a far more accurate expression of existence than realism's verisimilitude can ever achieve. Common experience is bizarre and unfathomable. Only habit keeps it from seeming so. I tie a string to a small creature, tie the other end to my hand, and walk in circles around assemblages of wood and stone where other people congregate and, in a hole filled with sharp and dull protuberances, grind the bodies of other creatures, in no small way similar to the one tied to my wrist, into a fine paste, which they then force inside themselves over and over until they can fit no more and the paste wanders through their bodies and pushes itself out. Once the small creature does the same, I can go to my own assemblage. I walk my dog around houses where people eat. Once it defecates, I can go home. The unreal allows one to see existence without the veil of habit. Realism allows one to see existence with an ever-reinforced veil of expectation. I suppose it's all in what one wants.